2021
DOI: 10.36740/wlek202101127
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria: Current Public Health Challenge in Ukraine and Worldwide (Literature Review)

Abstract: The aim: Of the paper is to analyze the current views on diagnosis and management of diphtheria in children. Materials and methods: The data of scientific literature have been analyzed, using the bibliosemantic method of study. Conclusions: The specific prophylaxis is recommended to prevent the infection. It has cross-protection against different strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Recent reports showed that Ukraine has a significantly lower vaccination level than Poland and most European countries [1]. They also observed 56 cases in 2010--2018 [15], which suggests the continuous presence of C. diphtheriae in the population inhabituating this geographical region. This is a new challenge for not only Polish healthcare but in the whole of Europe.…”
Section: Discussionmentioning
confidence: 98%
“…Recent reports showed that Ukraine has a significantly lower vaccination level than Poland and most European countries [1]. They also observed 56 cases in 2010--2018 [15], which suggests the continuous presence of C. diphtheriae in the population inhabituating this geographical region. This is a new challenge for not only Polish healthcare but in the whole of Europe.…”
Section: Discussionmentioning
confidence: 98%
“…In Ukraine, the MMR vaccine against measles, mumps and rubella is administered similarly to Poland in the form of 2 doses, at 12 months of age and at 6 years of age. The measles outbreak in Ukraine in 2017-2019 also had an impact on the state of immunization against this disease [6,10]. Most of the population is likely to have been exposed to the measles virus.…”
Section: Measlesmentioning
confidence: 99%
“…The WHO reports that epidemic situation in diphtheria morbidity has worsened in the world, particularly in Latin America, where a rise in incidence has been recorded since 1990s [10].…”
Section: Diphtheriamentioning
confidence: 99%